2015
DOI: 10.1186/s12906-016-0996-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine in patients with health complaints attributed to former dental amalgam fillings

Abstract: BackgroundThe dental filling material amalgam is generally well tolerated. However, a small proportion of dental patients experience health complaints which they attribute to amalgam. The symptom pattern is often similar to patients with medically unexplained physical symptoms (MUPS) and the health complaints may persist after amalgam removal. Among patients with MUPS, the use of complementary and alternative medicine (CAM) seems to be high. The aim of this survey was to describe the prevalence and range of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Even though conventional medicine is the officially approved medical system in Norway, many people choose additional modalities to improve their health or as a consolation in a challenging health situation [48–50]. Our study supports earlier findings showing that TM exists along with CM outside the official health care system [9, 51].…”
Section: Discussionsupporting
confidence: 89%
“…Even though conventional medicine is the officially approved medical system in Norway, many people choose additional modalities to improve their health or as a consolation in a challenging health situation [48–50]. Our study supports earlier findings showing that TM exists along with CM outside the official health care system [9, 51].…”
Section: Discussionsupporting
confidence: 89%
“…One of the aims of this program was to develop a rehabilitation program for patients who have had all their amalgam fillings removed, but still experienced symptoms. A part of this intervention should be based on a survey exploring the target groups’ experiences with different types of interventions that were not part of the official healthcare system in Norway [ 21 ]. The Norwegian Data Inspectorate (NSD) has been notified about the study and the Regional Committee for Medical and Health Research Ethics (REK) has considered the study (REK reference 2011/1281) and decided that no ethic approval was needed due to full anonymity of the participants.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The questionnaire asked for sociodemographic data, subjectively perceived health status, complaints persisting after amalgam removal (based on Norwegian version of the Giessen Subjective Complaints List (GBB-24)), self-reported changes in symptoms after amalgam removal, and experience with different therapeutic interventions. The questionnaire also asked for use of complementary and alternative therapies, which are reported elsewhere [ 22 ]. The only criteria for inclusion were membership in the patient association NDPA and previously amalgam fillings of which all were removed.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Kristoffersen et al (2016) concluded that alternative medicine was widely used in patients with health problems attributed to dental amalgam, as it is not an accepted diagnosis in the health care system. Clearly, alternative medicine has a broader and a more vague definition of disease; if you feel ill, choose to be ill, or have an illness behavior, then you have a disease (Johanisson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Patients commonly combine alternative healing systems with biomedical care to provide alternative explanations of illness (Asbring & Narvanen, 2004). Kristoffersen et al (2016) concluded that alternative medicine was widely used among patients with health problems attributed to dental amalgam.…”
Section: Discussionmentioning
confidence: 99%